The results of laboratory and instrumental methods for rotavirus infection in children - N. B. Denisyuk; Yu. D. Kagan (Журнал инфектологии, 2014)
The results of laboratory and imaging studies 128 patients with a diagnosis of early childhood rotavirus infection. Mono-rotavirus infection in 55,3% of cases proceeded with symptoms of gastroenteritis, severe dehydration accompanied by varying degrees of severity. Mixed-rotavirus infection in 53,5% of cases proceeded with a syndrome characterized by severe enteritis and toxic syndrome. In severe forms of rotavirus infection marked by dysfunction of the liver, pancreas, and the characteristic changes in biochemical and clinical parameters.